The influence of lecturers' verbal and non-verbal immediacy behaviour on perceived affective and cognitive learning - Terblanche, Lydie (University of the Free State, 2004)
The results indicated that the impact of the perceived immediacy operated differently for the two groups, although they should be interpreted with some degree of caution. There were significant relationships for the whole test group between learners' perceptions of lecturers' immediacy behaviour and learning. The verbal total score, the non-verbal total score, the immediacy total score as well as the majority of individual items showed significant relationships with learners' cognitive as well as affective learning. Verbal items, especially item 17 (Praises learners' work, behaviour or comments), showed a high correlation with the different learning variables (cognitive and affective). Regarding non-verbal items, item 23 in particular (Speaks in a monotonous or boring voice when he/she lectures) showed a high correlation with the different learning variables (cognitive and affective). The relationships between the verbal total scores and cognitive learning (simple learning and learning loss) variables were statistically significant for both Germanic and African learners. The correlations between the non-verbal total scores and the cognitive learning (simple learning and learning loss) variables were statistically significant for Germanic learners, but were not statistically significant in the African learners' group. Furthermore, the relationships between the immediacy total scores and the cognitive learning (simple learning and learning loss) variables were statistically significant for Germanic as well as African learners. Regarding the correlation between the verbal items and cognitive learning (learning and learning loss), numerous items were statistically significant for Germanic learners, while only some items showed such a relationship for African learners. In terms of the relationships between non-verbal items and cognitive learning (learning and learning loss), various items also showed a statistically significant relationship for Germanic learners, while only one item (item 32 - in simple learning) showed a significant relationship for African learners. The relationship between the non-verbal total scores and simple learning differed significantly between the two groups. The relationship between the non-verbal total score and learning loss also differed significantly between the two groups. The Germanic learners repeatedly showed a significantly higher relationship than that of the African learners. It was obvious that the relationship between the verbal item 4 (Uses humour in class) and simple learning differed significantly for the two groups and that the relationship between the same item and learning loss also differed significantly for the two groups. The Germanic learners showed a significantly higher relationship in comparison with African learners. The relationship between the non-verbal item 34 (Uses a variety of vocal expressions when he/she talks to the class) and simple learning differed significantly for the two groups. The relationship between the same item and learning loss also differed significantly between the two groups. The Germanic learners once again showed a significantly higher relationship in comparison with the African learners. The relationships between the verbal total scores and affective learning (attitude, behavioural intent and total affect) variables, as well as the relationships between the non-verbal total scores and affective learning variables, were statistically significant for Germanic learners, while these relationships were not statistically significant in the African learners' group. In contrast to cognitive learning, the relationship between the immediacy total scores in affective learning (attitude, behavioural intent and total affect) variables were only significant for Germanic learners. Concerning the correlation between the verbal items and affective learning (attitude, behavioural intent and total affect), many of the items showed a statistically significant relationship for Germanic learners, while only some items showed such a relationship for African learners. The same tendency occurred in terms of the correlation between the non-verbal items and affective learning (attitude, behavioural intent and total affect). The relationship between the verbal total scores and all three affective learning variables (attitude, behavioural intent and total affect) differed significantly for the two groups. The relationship between the immediacy total score and all three of the affective learning variables also differed significantly for the two groups. Again it was the Germanic learners who repeatedly showed a significantly higher relationship than that of the African learners. The relationships between numerous verbal items and all three affective learning variables differed significantly in the two groups. The verbal items in question were: item 4 (Uses humour in class) item 5 (Addresses learners by their names) item 6 (Addresses me by my name) item 11 (Gives feedback on my individual work by means of commenting on question papers, oral discussion, etc.) item 20 (Is addressed by his/her first name by the class) Germanic learners showed a significantly higher relationship in all these items when compared with African learners. The relationship between the non-verbal item 34 (Uses a variety of vocal expressions when he/she talks to the class) and all three affective learning variables differed significantly for the two groups. The Germanic learners once again showed a significantly higher relationship in comparison with the African learners. The most important differences between the two population groups exist mainly between the verbal items and the three affective learning variables. The significant relationships between lecturers' immediacy behaviour and learning (cognitive and affective) were present mainly for the Germanic learners, and only some of the immediacy items showed significant relationships with learning (cognitive and affective) variables for African learners. Pertaining to the size of effects, it can be observed that all the statistically significant coefficients showed a medium to large effect, which indicates that the findings have an average to large practical value. Differences occurred in means on two variables (item 6 and item 32) between African and Germanic learners. Noteworthy differences in terms of total scores on the immediacy of learning variables did not occur. Regarding item 6 (Addresses me by my name), the Germanic learners showed a higher mean in comparison with African learners. Both averages, however, showed that this form of lecturer behaviour occurs seldom or occasionally. Relating to item 32 (Has a very relaxed body posture when he/she is lecturing), the African learners showed a higher mean compared with Germanic learners. Both averages showed that this form of lecturer behaviour occurs fairly regularly. Even though the results indicated that the impact of perceived immediacy operated differently for the two groups (possibly due to the fact that cultures differ in terms of what they expect regarding other individuals' behaviour), this study indicates a significantly positive correlation between immediacy behaviour and cognitive, affective and behavioural learning. The research findings further prove that, in connection with the effect of immediacy behaviour on learning, both verbal and non-verbal immediacy behaviour are vital dimensions of effective instructional strategies for the promotion of affective and cognitive learning. In conclusion, the verbal and non-verbal immediacy behaviour of lecturers whose home language is Afrikaans or English contributes positively to the affective and cognitive learning of learners whose home language is Afrikaans, English, or one of the African languages. Ultimately, the immediacy behaviour displayed by English or Afrikaans lecturers functions differently for learners whose home language is one of the African languages, than for those whose home language is Afrikaans or English. The results of this study, in conjunction with the results of previous work on immediacy, indicate that teacher/instructor/lecturer immediacy has a significant influence on the learner-instructor/lecturer relationship. Moreover, the results of this study, combined with those of Fayer, Gorham and McCroskey (1988), Collier (1988) and Sanders and Wiseman (1990), indicate that the specific role of lecturer immediacy on learner outcomes was mediated, to some degree, by culture. As South African classrooms grow more culturally diverse, communication scientists should redouble their efforts in this promising area of research.
Keywords: Communication in education; Interaction anaylsis in education; Teacher-student relationships; Dissertation (M.A. (Communication and Information Studies))--University of the Free State, 2004